2 × 2 MIMO-OFDM-RoF generation and transmission of double V-Band signals using a microring resonator system - Amiri, I.S.; Alavi, S.E.; Soltanian, M.R.K.; Penny, R.; Supa'at, A.S.M.; Fisal, N.; Ahmad, Harith (Springer, 2016)
Multi-input multi-output (MIMO) signals have been all-optically generated via orthogonal frequency division multiplexing, and transmitted over a 50 km single mode fibre (SMF) optical link and also a 5 m 2 × 2 MIMO wireless link. The series of constituent single and multi-carrier optical soliton pulses, at frequencies of f1 = 192.6988, f2 = 192.7588, f3 = 192.79 and f4 = 192.84 THz that are applicable for radio over fibre (RoF) systems, were created using a microring resonator system. Sixty four multi-carriers with specific free spectral range of 109.37 MHz across a selected range of 192.7553–192.7623 THz were produced for the purpose of establishing two MIMO V-Band RF signals, and single carriers operating at f3 and f4 optically transported two separate MIMO signals over an RoF link. The optical single sideband with carrier modulation technique has been implemented so as to overcome RF power degradation. The resultant bit error rate (BER) calculation of overall system performance is discussed, and power penalties of 1.7 and 4.7 dB in 25 and 50 km SMF transmissions at the BER threshold respectively have been identified. The results of this research show that transmission of MIMO signals is feasible for up to a 50 km SMF path length and wireless distance of 3 m.